A microstrip antenna for Bluetooth, WLAN and X band communication applications using Defective Ground Structure (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article, a multi band antenna designed using FR-4 Epoxy as a substrate is introduced and discussed. The proposed antenna has a thickness of 1.6mm. A L shaped slot and a I shaped slot is etched on the metal portion of  the ground structure. The introduced antenna resonates at 2.6, 5.2, 7.3 and 9.4GHz frequencies which are useful for Bluetooth, Wireless Local Area Network and X band communication. The significance of the projected antenna is to obtain the parameters S11, VSWR, bandwidth, radiation   pattern and gain. The obtained result confirms that the designed antenna works good with the gain 3.57 to 5.52 dB with working bandwidth for VSWR less than  2.